Study on Graphite Powder as Conductive Pigments for Impressed Current Cathodic Protection System using Carbon Fiber Reinforced Polymer Anode - Gunawan Budi Wijaya; David Pratama Lays; Hongky Haodiwidjaya Tanto; Daniel Tjandra (Civil Engineering Dimension, 2019)
The use of Carbon Fiber Reinforced Polymer (CFRP), for both strengthening material and anode for Impressed Current Cathodic Protection (ICCP) system, is being investigated.  The focus of this study is to develop the epoxy that has good bond strength and electrical conductivity. Graphite powder is used as conductive pigments with percentage ranges from 7.5% to 17.5%.  All specimens were partially submerged in 5% NaCl solution and induced with electrical current of 10 mA/m2 and 20 mA/m2 for 30 days. An average potential increase of 200 mV was recorded using half cell potential test. The application of 30 days ICCP up to current density of 20 mA/m2 did not affect the bond strength significantly and still complies with ACI recommendation. However, graphite content of more than 15% are found to be not workable and the bond strength is greatly reduced to less than 1 MPa This study concluded that the recommended graphite powder content shall be in the range of 10% to 15%.